Finite-time stability criteria for a class of fractional-order neural networks with delay. Issue 3 (April 2016) - Chen, Liping; Liu, Cong; Wu, Ranchao; He, Yigang; Chai, Yi
Abstract Finite-time stabilities of a class of fractional-order neural networks delayed systems with order $$α {:}$$ α : $$0<α \le 0.5$$ 0 < α ≤ 0.5 and $$0.5<α <1$$ 0.5 < α < 1 are addressed in this paper, respectively. By using inequality technique, two new delay-dependent sufficient conditions ensuring stability of such fractional-order neural networks over a finite-time interval are obtained. Obtained conditions are less conservative than that given in the earlier references. Two numerical examples are given to show the effectiveness of our proposed method.